The Relationship between Internet Gaming Addiction and Sleep Quality in the Mobile Legend Bang-Bang Online Game Community - Irna Ramadhini, Fadilla; Saputra, Evan (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
Moment Indonesia is experiencing this development very technological _ fast , wrong One development such technology _ The fastest growing thing in Indonesia is online gaming. Research This own objective For know is there is connection between internet gaming addiction and quality Sleep on mobile legend bang-bang online game community . Study This use method quantitative . Respondent on research This as many as 100 people from the legend mobile online game community . Election respondent use purposive sampling technique , namely with set criteria certain as sample research . Data processing uses Pearson Product Moment correlation for prove hypothesis . From the results obtained that its sig (2-tailed ) value is 0.002. Which means 0.002 < 0.025 then Ho is rejected and Ha accepted so that obtained results exists connection between internet gaming addiction and quality sleep.